Productive efficiency of tilapia oreochromis sp Raised in geomembrane pond with biofloc and raceways technology: Eficiencia productiva de la tilapia oreochromis sp criados en estanque de geomembrana con tecnología biofloc y raceways (BISTUA Revista de la Facultad de Ciencias Básicas, 2025)
The study compared the productive efficiency of red tilapia raised in geomembrane ponds with biofloc and raceways technology. Key physicochemical parameters in both systems were analyzed, highlighting correlations between variables and their impact on water quality and fish performance. In biofloc, a moderate positive correlation was found between dissolved oxygen, pH and temperature, highlighting the importance of maintaining optimal oxygen levels. In raceways, a strong positive correlation was found between dissolved oxygen and pH, underlining the influence of pH on oxygen availability. No significant differences were found in feeding rates, feed conversion, mortality, and survival between the systems, indicating their equal productive efficiency and mortality control. These findings support that both biofloc and raceways are viable options for tilapia culture, with comparable results in water quality, fish performance and economic efficiency. This study can guide aquaculture producers in choosing the most appropriate culture system according to their specific needs and conditions.
Keywords: Aquaculture; Tilapia